Trial and error the advent and eclipse of Benazir Bhutto - Akhund, Iqbal (Oxford Oxford University Press, 2000)
On the life and political career of Benazir Bhutto, ex-prime minister of Pakistan.
Keywords: Bhutto, Benazir; Prime ministers -- Pakistan -- Biography; Pakistan -- Politics and government -- 1971-1988.; Pakistan -- Politics and government -- 1988-.